Effects of foreign aid, oil price and conflict on low-income OIC countries' economic growth - Niran, Adedeji Abdulkabir; Mat Ghani, Gairuzazmi; Ahmad Sidique, Shaufique Fahmi (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
The low-income member countries of the Organization of the Islamic Conference (OIC-LDCs) receive substantial amount of official development assistant (ODA) purposely to improve economic condition which is characteristically and persistently poor. 23 OIC-LDCs, being common ODA recipients were, selected over period 1960-2007. This paper investigate the effect ODA, oil-price increase and conflict on OIC-LDCs’ economic growth employing Fixed Effect Error Component (FEEC) technique. We found that little interrelationship exist between OIC-recipient countries’ GDP and ODA, which is consistent with Burnside and Dollar (2000, 2004) findings. The civil armed conflict is negatively related with GDP growth. We also found that a shock effect of $10 increase in price of crude oil per barrel, on average, will reduce oil-importing OIC member countries’ economic growth by 0.3%.